TEACHER'S STRATEGY IN INCREASING STUDENT LEARNING MOTIVATION AT NABIGH ACADEMIC PAUD IN SOPPENG REGENCY DURING THE COVID-19 PANDEMIC - Fadli, Zul; Amriadi, Amriadi; Rachmat, Zul; S, Wahyuddin (Jurnal Ekonomi Balance, 2021)
With regard to the Covid-19 pandemic, Nabigh Akademik PAUD teachers must change their teaching methods and strategies. This study aims to examine how the strategies of Nabigh Akademik PAUD teachers in increasing students' learning motivation, especially during the pandemic. This research method uses a descriptive method with a qualitative approach, where the research subjects are all PAUD Nabigh Akademik teachers. Data collection techniques used in this study were the following methods: (1) observation, (2) interviews, (3) documentation, and (4) literature study. The results of this study are the PAILKEM strategy is a strategy that can be relied on by teachers in carrying out the teaching and learning process, especially during the Covid-19 pandemic.